The association between facets of conscientiousness and performance‐based and informant‐rated cognition, affect, and activities in older adults. Issue 2 (28th July 2021) - Sutin, Angelina R.; Aschwanden, Damaris; Stephan, Yannick; Terracciano, Antonio
Abstract: Objective: To identify facets of conscientiousness associated with objective cognitive performance, informant‐rated cognitive decline, and informant‐rated affect and activities implicated in cognitive health. Method: Health and Retirement Study participants ( N  = 2, 516) reported on their personality, completed a comprehensive cognitive assessment, and had knowledgeable informants report on their cognition, affect, and activities. Results: Industriousness and responsibility were associated with better cognitive performance; order was associated with less informant‐rated cognitive decline. The facets were also associated with more positive affect, less negative affect, greater engagement in cognitive activities and activities outside the house, and less engagement in passive activities, as rated by a knowledgeable informant. Informant‐rated engagement in cognitive activities mediated the association between self‐reported responsibility and objective cognitive performance. Conclusions: Tendencies toward achievement and accountability were associated with healthier cognitive performance and daily profiles that support cognitive health, whereas organization was associated with cognition as reported by a knowledgeable informant. The differential pattern of correlates is informative for the theoretical processes that link distinct facets of conscientiousness to healthier cognitive aging.